Flow Control and Design Assessment for Drainage System at McMurdo Station, Antarctica - Affleck, Rosa; Carr, Meredith; West, Brendan (2014)
Runoff at McMurdo Station is driven primarily by the melting of snow and glacier ice. Snowmelt runoff passes through McMurdo via a system of drainage ditches, gullies, and culverts. Ultimately, the snowmelt runoff discharges into Winter Quarters Bay and McMurdo Sound through several discharge points. Although the most extreme runoff, during heavy flow has not been measured, we have observed that the runoff mobilizes sediment, erodes the drainage channels and embankments, and overflows onto roads. The objectives of this study were to manage flow; to minimize erosion; and to improve the drainage system by modeling high flows, designing control measures, and evaluating existing culvert and snow dump locations at McMurdo Station. Flow modeling and structural analyses were conducted to determine design parameters for control measures, including rock and wooden weirs; to evaluate various design alternatives against erosion control metrics; to evaluate culvert conditions; and to investigate an alternative flow path and sediment ponds. A qualitative review of culvert conditions and snow dump locations was also performed. This report identifies specific mitigation recommendations using these control measures, which will help prevent future overflow and deterioration of the McMurdo drainage system. The original document contains color images.